A neurotoxic glycerophosphocholine impacts PtdIns-4, 5-bisphosphate and TORC2 signaling by altering ceramide biosynthesis in yeast. - Michael A Kennedy; Kenneth Gable; Karolina Niewola-Staszkowska; Susana Abreu; Anne Johnston; Linda J Harris; Fulvio Reggiori; Robbie Loewith; Teresa Dunn; Steffany A L Bennett; Kristin Baetz (PLoS Genetics, 2014)
Unbiased lipidomic approaches have identified impairments in glycerophosphocholine second messenger metabolism in patients with Alzheimer's disease. Specifically, we have shown that amyloid-β42 signals the intraneuronal accumulation of PC(O-16:0/2:0) which is associated with neurotoxicity. Similar to neuronal cells, intracellular accumulation of PC(O-16:0/2:0) is also toxic to Saccharomyces cerevisiae, making yeast an excellent model to decipher the pathological effects of this lipid. We previously reported that phospholipase D, a phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2)-binding protein, was relocalized in response to PC(O-16:0/2:0), suggesting that this neurotoxic lipid may remodel lipid signaling networks. Here we show that PC(O-16:0/2:0) regulates the distribution of the PtdIns(4)P 5-kinase Mss4 and its product PtdIns(4,5)P2 leading to the formation of invaginations at the plasma membrane (PM). We further demonstrate that the effects of PC(O-16:0/2:0) on the distribution of PM PtdIns(4,5)P2 pools are in part mediated by changes in the biosynthesis of long chain bases (LCBs) and ceramides. A combination of genetic, biochemical and cell imaging approaches revealed that PC(O-16:0/2:0) is also a potent inhibitor of signaling through the Target of rampamycin complex 2 (TORC2). Together, these data provide mechanistic insight into how specific disruptions in phosphocholine second messenger metabolism associated with Alzheimer's disease may trigger larger network-wide disruptions in ceramide and phosphoinositide second messenger biosynthesis and signaling which have been previously implicated in disease progression.